A high-performance energy storage system from sphagnum uptake waste LIBs with negative greenhouse-gas emission. (January 2020) - Liu, Yiyang; Ge, Zhen; Sun, Zhenhe; Zhang, Yan; Dong, Caiqiao; Zhang, Mingtao; Li, Zhongjun; Chen, Yongsheng
Abstract: The ever-growing energy market demands a million tons yield of lithium-ion batteries (LIBs) which contributes to the climate change via huge greenhouse gas (GHG) emission, yet the depleting cathode resources pursuit sustainable production routes. Recycling of the spent LIBs is crucial. Current LIBs recycling utilizes complex process and consumes huge amount of energy. The key question is how to balance the GHG emission and the overall performance of the recycled cathodes. Many techniques have been tried to address the issue, but the GHG-performance dilemma remains to be overcome. Here we provide a route of sphagnum uptake of spent LIBs cathode toward high performance lithium sulfur (Li–S) battery, which may settle the infeasibility of ternary cathode recycling via industrial applicable processes. As-prepared cathode benefits from both chemical stabilization and hierarchical structural encapsulation, hence grants high S ratio (~80%) and good specific capacity (~700 mA h g −1 after 300 cycles). Eventually, this route realizes an unprecedented negative GHG emission and achieves about 230% specific capacity higher than others. Graphical abstract: Sphagnum uptake spent Li-NCM ions can achieve dual-encapsulation for high performance Li–S battery. Image 1 Highlights: A negative GHG emission technique was developed with 230% higher specific capacitance (~700 mA h g -1 after 300 cycles) compare to other recycling methods. Uptake of sphagnum can naturally recycle waste LIBs via an ion-exchange mechanism As-prepared cathode grants tubular conductive highway which can facilitate the electron transfer, enlarge the sulfur loading, and accommodate the volume expansion. Physical & chemical dual-encapsulation of lithium polysulfides (LiPSs) was enabled by hierarchical porous structure and relatively high entropy metal oxides.